Validation of a scale to measure consumers’ perceptions of clothing retailers' corporate social responsibility (CSR) in South Africa - Taljaard-Swart, Hanri (University of Pretoria, 2021)
Dissertation (MSc Consumer Science (Clothing Management))--University of Pretoria, 2020.